Parental Perception of Fever in Children - Al-Khalidy, Mohammed , J; Thaher, Mahmood; Abdul Hameed, Ban (AL-Kindy College Medical Journal, 2007)
Back ground : Fever is a common medical problem in children. parents have been shown unrealistic fears of harmful effects of fever in their children. Resulting in inappropriate management of fever in their children. Objective: the objective of this study was to survey parents about their knowledge andattitude concerning fever in their children. Methods : The study involved random selection of parents who brought their febrile children to emergency department or out-patient clinics of five teaching and non teaching hospitals in Baghdad from first of October to end of December 2002. Parents of 400 febrile children were interviewed using a standard questionnaire to obtain sociodemographic information and current knowledge of fever. Results: Approximately 69% of the respondents were female, 68% their age was in the range of 21-35 years. Seventy seven percent of parents had two or more children. More than 70% of parents demonstrated a poor understanding of definition of fever , maximum temperature of untreated fever and threshold temperature requiring antipyretics . Twenty sevev percent of parents considered temperature less than 38.0 c o to be fever, another 27% did not know, the definition of fever, 61% felt that temperature of less than 40,0 c o could be dangerous to a child, and 27% could not define high fever. Another 28% believed that if left untreated, temperature could rise to 42.0 c o or higher, but 39% could not provide an answer, and about 60% did not know the minimum temperature for administering antipyretics. And 60% did not know the minimum temperature for bathing , or sponging. Approximately 93% of parents demonstrated fear of consequent body damage from fever , including convulsion ,brain damage ,coma, blindness and even death. Conclusion: parental misconception about fever reflects the lack of active health education. Health professionals have apparently not done enough to educate parents on this common medical problem and it, s consequences